How consumer ecocentrism, altruism, and subjective norms drive green consumption behavior through the synergistic effect of value internalization - Liu, Shang; Chen, Sze-Ting (Edelweiss Applied Science and Technology, 2025)
In the context of global ecological crises, promoting green consumption has become a vital issue for sustainable development. Existing research primarily emphasizes external factors, with limited exploration of the dual roles of endogenous consumer values and normative pressures. Particularly, there is a lack of systematic examination of the mediating pathways of green perceived value (GPV). This study, based on the Stimulus-Organism-Response (SOR) theory, models how consumer ecocentrism, altruism, and subjective norms influence green buying behavior (GBB) through the mediating role of GPV. Structural equation modeling was employed to analyze 1,076 valid questionnaires from Chinese consumers. The results indicate that ecocentrism, altruism, and subjective norms positively impact green consumption behavior and significantly enhance GPV. Moreover, GPV mediates the relationships between these three antecedents and GBB, while viral marketing moderates the link between GPV and GBB. This research provides strategic insights for businesses facing intense competition, extends the application of the SOR model and the Theory of Planned Behavior (TPB) in consumer behavior research, enriches the literature on consumer ecocentrism, and underscores the importance of governmental efforts to improve institutional environments and infrastructure to promote green consumption.